Regional insertion and the centrality of the small municipality: the case of Piraúba-MG - Vidal, Angélica Arruda; Itamar Caixeiro Stephan, Ítalo (Revista Nacional de Gerenciamento de Cidades, 2022)
It is commonplace for cities to be classified according to their size. Qualifying them as small, medium, or large is a social practice that concerns the subject's relationship with space. To define not only the size but the dynamics that engender the small town, it is necessary to analyze its regional insertion and the modifications that occur in the urban space from this, as well as the consequences of the refunctionalization processes in the wake of urbanization, evaluating what remains and what is changed in the urban characteristics of small towns. To carry out this analysis, we used as our field of study the municipality of Piraúba, located in the Zona da Mata of Minas Gerais. It is a local center, according to REGIC (2020). It is inserted in the divisions: the Intermediate Geographic Region of Juiz de Fora, in the Immediate Geographic Region of Ubá and is part of the Local Productive Arrangement, focused on furniture production. This work has as its main objective to reflect on the impact of the region on the economic performance and urban development of the small town. The study proves the debates about how the role of cities, when organized in a network, reverberates in its socioeconomic dimension in view of how Piraúba is both a small town polarized by larger centers and part of productive processes that grant it a polarizing force in relation to other small towns in its surroundings.